Ответы и объяснения

Лучший Ответ!
2013-11-29T16:32:59+04:00
В)х/6-2=х/4 +1       г)х/4+2=х/10-1            д)5-х/2-х/4=х+х/3
х/6-х/4=1+2           х/4-х/10=-1-2                 -х/2-х/4-х-х/3=-5
2х/12-3х/12=3        5х/20-2х/20=-3              -6х/12-3х/12-12х/12-4х/12=-5
-х/12=3                  3х/20=-3                      -25х/12=-5
-х=3*12                  3х=-3*20                     -25х=-5*12
-х=36                     3х=-60                        -25х=-60
х=-36                     х=-20                          х=60/25
                                                                х=две целых 2/5